2022
DOI: 10.1590/fst.43422
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hydrogels based on nanocellulose from garlic straw and regulating the release of allicin and its cytotoxicity

Xudong GAO,
Yanan JIA,
Zhongqin CHEN
et al.

Abstract: Allicin is an organosulfur compound found in garlic, which is well known for their anticancer properties, however, its application was limited due to its instability towards light, heat, and alkaline conditions. In order to improve the bioavailability and stability of allicin, allicin was loaded into the garlic straw nanocellulose hydrogels and its physiochemical properties and toxicity towards normal hepatocyte cells (L02) and cancerous cells (HepG2) were evaluated. Initially, garlic straw was used as raw mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The peak at 2920 cm −1 , more prominent in the UCF spectrum, corresponds to the stretching vibrations of C-H from the methyl and methylene groups of lignin and hemicellulose [16,18]. The reduction observed in the TCF indicates the partial removal of these components.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 98%
“…The peak at 2920 cm −1 , more prominent in the UCF spectrum, corresponds to the stretching vibrations of C-H from the methyl and methylene groups of lignin and hemicellulose [16,18]. The reduction observed in the TCF indicates the partial removal of these components.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 98%
“…The composite hydrogels exhibited high stability, cumulative release behavior, and an antifungal effect. Gao et al developed a garlic straw nanocellulose (GSNC) based hydrogel with a particle size of 168.0 ± 0.65 nm, a loading capacity of 166.4 mg/g, and an EE of 83.20% . The cell experiment showed that the GSNC hydrogel could help allicin enter the cell membrane, improve its bioavailability, and significantly enhance its inhibition effect on cell proliferation compared to free allicin in HepG2 cells.…”
Section: Delivery Systemsmentioning
confidence: 99%
“…Garlic waste materials, such as husk, peel, stem, or straw, are materials that do not have an industrial application, despite having interesting properties. Some works report the use of garlic husk (GH) as a source of phenolic compounds [ 27 ], for edible films [ 28 , 29 , 30 , 31 , 32 ], and nanocellulose extraction [ 33 ], which are some of the explored options for this waste material. GH is one of the garlic waste materials that is a promising additive for polymer matrices.…”
Section: Introductionmentioning
confidence: 99%